Labor in the rural household economy of the Zairian basin - Tshibaka, Tshikala B. (International Food Policy Research Institute, 1992)
Previous labor studies conducted in Sub-Saharan Africa have tended to concentrate mostly on describing the division of labor, estimating the amount of labor allocated to agriculture and other household activities, examining the seasonality of labor time spent on agriculture, and estimating the productivity of labor input and the contribution of this input to farm output. It is clear from a survey of the literature that these labor studies have largely overlooked two other significant aspects of labor allocation and use in Sub-Saharan agriculture. First, they did not pay enough attention to the effects of economic variables on labor use and allocation. Second, they did not examine the effect of the timing of various farm operations on the amount and productivity of labor used. Labor in the Rural Household Economy of the Zairian Basin, Research Report 90, by Tshikala B. Tshibaka, addresses these gaps and contributes to an understanding of the rural household economy in this tropical rain forest area, one of the least-known parts of the developing world. This analysis is derived from data collected in an extensive 1982/83 household survey by the author in collaboration with the Institut Facultaire des Sciences Agronomiques, Yangambi, Zaire. In addition to the aspects of labor use addressed in earlier studies, this study attempts to identify the key economic and other variables that affect the use and productivity of labor in the small-farm sector of the Zairian Basin.